Soil physical quality in agricultural systems on the Cerrado of Piauí State, Brazil - Schossler, Thiago Rodrigo (2018)
Soil quality is essential for maintaining the sustainability of agro-ecosystems and ecosystem services provided by this natural resource. The present study aimed to assess the physical quality of soil through the characterization of the physical properties in grain production systems in the Southwest region of Piauí State, Brazil. The study was carried out in the Cerrado region of Piauí in four cities in areas of expansion of the agricultural frontier of the state: Baixa Grande do Ribeiro, Sebastião Leal, Uruçuí and Bom Jesus. Soil samples were collected in April 2012, in areas of grain production under conventional and no-tillage systems. Adjacent areas with native vegetation were also sampled as reference. Bulk density, effective saturation, hydraulic conductivity, penetration resistance, porosity and aggregation were measured. Regardless of the type of soil management used, agricultural systems degrade soil physical quality. No-tillage showed higher bulk density, penetration resistance and aggregation, with lower total porosity, macroporosity and hydraulic conductivity. The physical quality of soil in the agricultural areas of the Cerrado region of Piauí was dependent on the soil texture, while silt, clay and organic matter were determinant for soil aggregation, mechanical resistance, total porosity and microporosity.